Basal and bevacizumab-based therapy-induced changes of lactate dehydrogenases and fibrinogen levels and clinical outcome of previously untreated metastatic colorectal cancer patients: a multicentric retrospective analysis. (February 2015) - Silvestris, Nicola; Scartozzi, Mario; Graziano, Giusi; Santini, Daniele; Lorusso, Vito; Maiello, Evaristo; Barni, Sandro; Cinieri, Saverio; Loupakis, Fotios; Pisconti, Salvatore; Brunetti, Anna Elisabetta; Palasciano, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Background: To assess the predictive role of lactate dehydrogenases (LDH) and fibrinogen (FBG) serum levels in metastatic colorectal cancer (mCRC) patients receiving a first-line bevacizumab-based therapy. Objectives: The aim of the present analysis was to retrospectively evaluate the role of basal and post-treatment LDH and FBG serum levels in predicting the clinical outcome of 139 mCRC patients receiving first-line chemotherapy in combination with bevacizumab. Results: A statistically significant association between high pre-treatment LDH and FBG levels and progressive disease was observed with respect to low basal LDH and FBG patients. Furthermore, median progression-free survival was 7.3 versus 10.8 months and 7.3 versus 9.4 months for high and low LDH and FBG levels, respectively. Within the high LDH group, we observed a statistically significant reduction of LDH mean value compared with pre-treatment values in patients with objective response rate and stable disease. Conclusions: High LDH and FBG levels correlated with prognosis. A significant correlation between bevacizumab-based chemotherapy-induced reduction in LDH serum levels and response to treatment was observed within the high LDH group. These results, if confirmed in larger prospective studies, could be helpful for early identification of patients responsive to bevacizumab-based chemotherapy or candidate to more aggressive treatments.